IDEOLOGI KIRI DALAM FILM LA FAUTE Ã FIDEL - , ANDREAS AVL NOVA K, Wulan Tri Astuti, S.S, M.A ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Since its inception, film has become the medium of human speech as a transmitter of communication, as well as perpetuating what humans have done for thousands of years, which is to tell the story. Similar to literature, movie can be used to represent the realities. The ability of the movie to represent reality, often used to represent a discourse. The discourse represented in the movie is often loaded by ideology, then the film can be used as a propaganda. The research, entitled «The Ideology of the Left in the film La Faute à Fidel» reveals how ideologies are represented in that film. The material object of this research is a film directed by Julie Gavras, La Faute à Fidel (2006). The film is adapted from the novel Tutta Colpa di Fidel written by francoitalien writer, Domitia Calamai. This film tells the story of Anna de la Mesa, a nineyear- old girl, who is trapped in the shifting point of political ideology of her parents. This 90-minutes film explicitly filled by a lot of ideologies. The qualitative research methods is used to track ideology which is hiding behind cinematic elements, and reveals how the film represents the ideology.